Adaptation To Changes In Coal Quality: Case Study At PT Paiton Energi (PE) - Satyo Jati Prakoso; Widayat Widayat; Sri Widodo Agung Suedy (Eduvest - Journal of Universal Studies, 2024)
This study discusses the coal conversion project undertaken by Paiton Energy (PE) in Indonesia in response to changes in coal supply. The root cause analysis method is used to systematically map PE case studies. The results show that PE has successfully adapted to changes in coal quality through the coal conversion project, but faces new challenges with the increasingly limited reserves of high-quality coal in the future. Therefore, further adaptation measures are needed to ensure the sustainability of power plant operations in the future.